Dificultades y peculiaridades de la traducción de términos agrícolas en la combinación lingüística francés-español - Tijeras López, Entiqueta (Anales de Filología Francesa, 2010)
The scientific-technical language occupies a very large plot within the field of translation studies. However, the problem of translation of agricultural terms, specifically within the French-Spanish language pair, is a subject still little addressed by both professional translators and in the curricula of Spanish universities. It is through the analysis of different types of documents that all the translation problems and linguistic difficulties will be raised. Among the most important documents, we can mention: technical files of agricultural products (either to the producer or the consumer), contracts related to the production, use and export of agricultural products, etc. The economic sectors related to agriculture in the province of Almería have raised a need to facilitate communication with customers or suppliers from other countries, so developing an accurate terminological and textual (bilingual) database is essential and its elaboration will be the object of our study.